A panel of bovine, ovine and caprine polymorphic microsatellites - Kemp, Stephen J.; Brezinsky, L.; Teale, A.J. (Wiley, 1993)
We report a set of six new bovine microsatellite polymorphisms based on (CA)n repeats. They are highly polymorphic and thus represent valuable markers for genome mapping. Four of the six are polymorphic in sheep and two are polymorphic in goats. One, which is polymorphic in cattle and sheep and apparently monomorphic in goats, is X‐chromosome specific and has potential value in, for example, sex determination and detection of chimaerism.